Media Literacy Levels of Archivists in Institut Teknologi Sepuluh Nopember (ITS) - Agus Santoso; Isminarti, Isminarti (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
Media literacy is a concept that describes a person’s ability to utilize media, analyze information, and communicate it. This concept is used by researchers to see a person’s ability to relate to information media. This study discusses the level of media literacy of archivists in the Institut Teknologi Sepuluh Nopember (ITS). The archivist has a strategic position in information management of the university. In this respect, it needs to be reviewed related to the competence of the media literacy of archivists. In this era of information, archivists are faced with various job challenges due to the development of information technology, including the fast in disseminating information and the emergence of false or misleading information (hoaxes). This condition causes archivists not only to be required to have competence in utilizing information technology but also to be able to analyze and communicate information correctly to provide a fast, accurate, and reliable service. This competency will be reflected in the level of media literacy of archivists. This research uses the descriptive quantitative method by focusing on the aspects of a phenomenon and the reality of media literacy by archivists in ITS. The level of media literacy can be seen from the Individual competence framework presented by the European Commission (2009). The result of the study showed that the media literacy of archivists in ITS is at a medium level, which indicated the competence is more focused on the ability of technical skill and critical understanding. While in the social competence aspect are classified as passive users.